Periosteal Stripping Induces Comparable Early Callus Formation but Late-Phase Regression: A Histomorphometric and Machine-Learning Analysis in a Rat Femoral Fracture Model - Chandra Budi Hartono; Udi Herunefi Hancoro; Ida Bagus Budhi Surya Adnyana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The periosteum is critical for fracture healing, serving as a reservoir for osteoprogenitor cells and vascular supply. A clinical paradox exists where periosteal stripping is considered detrimental yet is historically associated with hypertrophic overgrowth. This study investigates the temporal paradox of periosteal stripping, testing the hypothesis that it induces a biphasic response characterized by early inflammatory compensation followed by late-phase regenerative failure. Methods: Twenty-four male Sprague-Dawley rats were randomized into four groups (n=6/group): Intact Periosteum (PI) and Periosteal Stripping (PS), evaluated at 14 and 28 days post-fracture. Mid-diaphyseal femoral fractures were stabilized with 1.0 mm K-wires. Healing was quantified using a validated Modified Allen-Huo Histological Score (0-10) and Trainable Weka Segmentation (TWS) for tissue classification. Osteoclast activity was assessed via Tartrate-Resistant Acid Phosphatase (TRAP) staining. Results: At Day 14, the PS group exhibited healing comparable to the PI group (Median Score: 8.0 [IQR 8.0–9.0] vs. 8.0 [IQR 7.0–8.0]; p = 0.176), driven by hypertrophic soft callus formation rather than true osteogenesis. However, by Day 28, the PS group demonstrated significant regression (Median Score: 3.5 [IQR 3.0–4.8]) compared to the PI group (Median Score: 8.0 [IQR 8.0–8.0]; p = 0.006). Quantitative histomorphometry revealed significantly higher osteoclast density in the PS-28 group (TRAP+ cells: 18.5 ± 2.1/field) compared to PI-28 (4.2 ± 1.1/field; p < 0.001), indicating active resorption of the unstable callus. Conclusion: Periosteal stripping does not accelerate early healing but induces a volume-matched inflammatory callus that fails to consolidate. The significant late-phase regression underscores the vital role of the cambium layer in definitive remodeling. Surgical preservation of the periosteum is mandated to prevent atrophic non-union.